Effect of fully restrained beam-to-column connection on the progressive collapse strength of steel moment frames. Issue 8 (June 2020) - Salmasi, Alireza; Sheidaii, Mohammad Reza; Saghaie Sahebalzaman, Mohammad; Tariverdilo, Saeed
The beam-to-column connection has been identified as a key element for steel frame structures to maintain the structural integrity during progressive collapse phenomenon. In the current study, in order to assess the effects of beam-to-column connection type on the progressive collapse strength of steel moment frames, the progressive collapse behavior of a steel intermediate moment frame structure was evaluated with 10 different types of fully restrained connections. The progressive collapse strength of these buildings against sudden removal of a column was separately studied using nonlinear static alternate path method presented in Unified Facility Criteria progressive collapse guideline. To consider the nonlinear effects in the structural modeling, plastic hinges for beam and column members and connections were defined and modeled according to the ASCE 41 standard. The results of the progressive collapse analyses indicated that if the plastic hinges of connections are separately defined in addition to the plastic hinges of beams and columns, the structure will have lower progressive collapse strength, and the calculated dynamic increase factor will grow. Among the studied types of connections, the free flange connection had the best performance and the highest strength against progressive collapse.